Papéis e atividades dos orquestradores de ecossistemas regionais de inovação: um estudo de caso com o programa Inova RS - Tubin, Lucieli Cátia (Universidade do Vale do Rio dos Sinos, 2023)
This study was developed to address a gap in the literature regarding the activities of regional innovation ecosystem orchestrators (ERIs). Understanding these activities is essential for promoting the development of ERIs, which can accelerate the transformation of cities and regions. There is a set of factors that need to be combined for the effective establishment of an innovation ecosystem. This work aims to understand the main roles and activities of orchestrators in regional innovation ecosystems. In this study, a case study method was chosen, focusing on the "Inova RS" program launched in 2019 by the Department of Innovation, Science, and Technology (SICT) of the government of Rio Grande do Sul. The goal of this program was to integrate the state of Rio Grande do Sul into the global innovation landscape. A qualitative exploratory approach was adopted, focusing on four regional innovation ecosystems (ERIs): two that were more developed and two that were less developed, from the perspective of the program. The theoretical foundation of this study was constructed through a systematic literature review, encompassing concepts such as innovation ecosystems, orchestration, quadruple helix, and the various dimensions of orchestration. Data collection was conducted through both secondary and primary data, including fourteen interviews with key stakeholders representing the program at the state level and the four units of analysis. The mapping of the interviewees was conducted using the snowball technique and revealed that most coordinators were associated with the academic helix. The criteria adopted for this definition, according to the program managers, were the involvement of actors in the ERI, the integration of the educational helix of the macro-region, understanding the purpose of the program, and generating a sense of belonging among stakeholders. The overall objective of the research was to understand the main roles and the key activities of regional innovation ecosystem coordinators. The study advances beyond previous research by expanding the "orchestration" model and validating its applicability in the context of the case study, which unfolds in eight regional innovation ecosystems. Therefore, unlike previous studies, the applicability of elements in regional innovation ecosystem contexts is observed. The analysis revealed the presence of the seven dimensions of orchestration in "Inova RS" and identified twenty-nine key activities. Furthermore, it was observed that coordinators who receive government grants, known as Innovation and Technology Managers (GITs), have a more consistent role. The study also highlighted various factors that affect the orchestration of ERIs, with an emphasis on the role of universities, events, innovation readiness, communication, knowledge, and the importance of knowledge management, as well as the concept of coopetition (collaboration versus competition). Based on these findings, the study contributed with four propositions addressing prerequisites, leveraging, and consolidating ERIs. Finally, based on field inferences, eight new key activities emerged that can assist public and private managers in the development and strengthening of Regional Innovation Ecosystems.
Keywords: Ecossistemas regionais de inovação; Orquestração; Papéis dos orquestradores; Atividades-chave; Regional innovation ecosystems; Orchestration; Key activities; Main roles; ACCNPQ::Ciências Sociais Aplicadas::Administração